1986
DOI: 10.1071/pp9860699
|View full text |Cite
|
Sign up to set email alerts
|

N2-Fixation in Field Settings: Estimations Based on Natural 15N Abundance

Abstract: This paper reviews a growing body of literature on the use of variations in the natural abundance of 15N to estimate the fractional contribution of N2-fixation to N2-fixing systems. This method is based on the small difference in 15NN abundance which frequently occurs between N derived from N2-fixation and N derived from other sources. The requirement of the method is that this difference be significant. Whether this requirement is met is site specific and must be empirically established at each site of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
710
5
17

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 569 publications
(746 citation statements)
references
References 93 publications
14
710
5
17
Order By: Relevance
“…A contribuição da FBN foi quantificada, para a cultura da soja, pela técnica de diluição isotópica de 15 N, baseada na abundância natural desse isótopo (Shearer & Kohl, 1986). Além das amostras da parte aérea das plantas de soja, obtidas no estádio R6, espécies espontâneas, não-leguminosas, foram também coletadas das mesmas parcelas para serem utilizadas como referência da abundância natural de 15 N do N disponível no solo.…”
Section: Methodsunclassified
“…A contribuição da FBN foi quantificada, para a cultura da soja, pela técnica de diluição isotópica de 15 N, baseada na abundância natural desse isótopo (Shearer & Kohl, 1986). Além das amostras da parte aérea das plantas de soja, obtidas no estádio R6, espécies espontâneas, não-leguminosas, foram também coletadas das mesmas parcelas para serem utilizadas como referência da abundância natural de 15 N do N disponível no solo.…”
Section: Methodsunclassified
“…The d 15 N values were significantly larger in pure grass than in mixed samples. This is most likely due to N fixation by legumes in mixed samples, which yields a lower isotopic value than N from soil sources (Högberg 1997;Shearer and Kohl 1986). Temperton et al (2007) have shown that legumes may also lead to lower 15 N signatures of neighbouring species, probably mainly through reduced competition for soil N. The difference between tall and short mixed vegetation was probably caused by the smaller relative biomass of legumes, mainly Trifolium repens, and thus smaller impact in tall vegetation patches.…”
Section: Isotopic Valuesmentioning
confidence: 98%
“…Plant shoot was oven-dried (60 o C) for the determination of dry mass and N and C concentrations were measured by mass spectrometry using the sampling preparation procedures described by Trivelin et al (1973). The biological nitrogen fixation (BNF) by leguminous plants was determined by natural abundance of 15 N technique (δ 15 N) (Shearer and Kohl, 1986), and sunflower was the non-N fixing specie. The chemical analysis of plants to determine macro and micronutrient contents were performed according to the methods proposed by Bataglia et al (1983).…”
Section: Methodsmentioning
confidence: 99%